Pemantauan intensitas lahan terbangun dan dampaknya terhadap albedo dan suhu permukaan lahan di Jakarta - Dibyanti Danniswari; Rian Adetiya Pratiwi; Olivia Seanders (Prodi Arsitektur Lanskap, Fakultas Pertanian, Universitas Udayana, 2025)
Urban expansion significantly alters surface characteristics, leading to changes in albedo and land surface temperature (LST) that contribute to the urban heat island phenomenon. This study aims to monitor the intensity of built-up land in Jakarta using the Modified Built-up Index (MBUI) and to analyze its relationship with surface albedo and LST over a ten-year period (2014–2024). Landsat-8 data were processed in Google Earth Engine to retrieve MBUI, albedo, and LST. The results reveal that MBUI and LST are negatively correlated, as expected, while MBUI–albedo and LST–albedo exhibit positive correlations, which contradict many previous studies. These findings suggest that built-up materials in Jakarta generally have higher albedo compared to vegetation and water bodies, a condition that may differ from other urban contexts. This highlights the unique role of material composition and urban morphology in shaping the city’s thermal environment. Overall, the study demonstrates the effectiveness of MBUI for monitoring urban built-up intensity and highlights the importance of integrating material properties, vegetation, and urban form to better understand and mitigate UHI impacts.